Improving Environmental Sustainability: A Geolocation-Based Mobile Application to Optimize the Recycling Process - Iparraguirre-Villanueva, Orlando (2023)
Environmental pollution caused by human activities is a global concern, and recycling is an effective strategy to reduce waste and minimize its negative impact on the environment, as these pollutants can have detrimental impact on ecosystems, human health, and the quality of life in general. Recycling avoids the accumulation of waste in landfills, which can contami-nate soil, water, and air as well as reducing the production of new products. The objective of this work is to implement a mobile application to improve waste management by recycling companies. The Mobile-D methodology was used for the development of the project because it focuses on optimizing the efficiency and performance of mobile applications since it allows working in 5 phases which are: Exploration, Initialization, Production, Stabilization and Testing. In the first indicator (KPI-1), an improvement in customer retention was observed, with an increase of 114.29% in positive responses in the post-test. In the second indicator (KPI-2), there was a 39.92% decrease in response time, indicating a faster response in the col-lection service. In the third indicator (KPI-3), a significant increase of 86.86% in the volume of waste for recycling was observed. The results showed improvements in all indicators, indicat-ing a positive impact of the implementation of the mobile application on waste management by the companies in the sector.